Case report: Oligodendroglioma, IDH-mutant and 1p/19q-codeleted, associated with a germline mutation in PMS2 - Merchant, Mythili; Raygada, Margarita; Pang, Ying; Quezado, Martha; Raffeld, Mark; Xi, Liqiang; Kim, Jung; Tyagi, Manoj; Abdullaev, Zied; Kim, Olga; Sergi, Zach; Pillai, Tina; et al. (Frontiers in Oncology, 2022)
Most tumors, including brain tumors, are sporadic. However, a small subset of CNS tumors are associated with hereditary cancer conditions like Lynch Syndrome (LS). Here, we present a case of an oligodendroglioma, IDH-mutant and 1p/19q-codeleted, and LS with a germline pathogenic PMS2 mutation. To our knowledge, this has only been reported in a few cases in the literature. While the family history is less typical of LS, previous studies have indicated the absence of a significant family history in patient cohorts with PMS2 mutations due to its low penetrance. Notably, only a handful of studies have worked on characterizing PMS2 mutations in LS, and even fewer have looked at these mutations in the context of brain tumor development. This report aims to add to the limited literature on germline PMS2 mutations and oligodendrogliomas. It highlights the importance of genetic testing in neuro-oncology.